Intelligence in health: A critical analysis strategy for decision-making in the health area: Inteligencia en salud: Una estrategia de análisis crítico para la toma de decisiones en el sector de salud - Figueroa Uribe, Augusto F. (2022)
The last year and a half, it was shown that the lack of use of data and information of origin in the health sector, produced one of the greatest catastrophes that humanity has experienced in the last 100 years. The aforementioned, due to a failure of vision, which unfortunately is seen as a problem not only of national security, but also of human security. Intelligence is the discipline that carries out the planning, collection, analysis and generation of products for the decision-making of the leaders of a country, sector, organization or society. This can be used very well in the health sector, applying the intelligence cycle model used in the security or financial field. That is, generating products from the analysis of raw information, lines of action, strategies and prospective scenarios that guide the decision maker to carry out health policies that comply with the human security strategies recommended by the United Nations Organization (UN) for a sustainable development.